Pengaruh Edukasi Prakonsepsi terhadap Perilaku Premarital Check Up pada Calon Pengantin di Kota Bandung - Nezima, Zilca (Politeknik Kesehatan Kemenkes Bandung, 2024)
Background: The postpartum period is a physiological thing experienced by every mother after giving birth and has an impact on physiological and psychological changes in postpartum mothers. One of the most common complaints experienced by postpartum mothers is fatigue. Symptoms of fatigue occur in around 64% of mothers in the postpartum period. It is reported that 75% of 10 postpartum mothers experience fatigue such as frequent yawning, stiff backs, unbalanced when standing and 25% say mothers have difficulty concentrating. Non-pharmacological therapy is needed to reduce fatigue in postpartum mothers, one of which is the effleurage hand massage technique with lavender aromatherapy. The combination of aromatherapy and massage in postpartum mothers can reduce the fatigue felt by the mother. Purpose: To determine the effectiveness of effleurage hand massage with lavender aromatherapy to reduce fatigue in postpartum mothers. Method: Case study on postpartum mothers using e-data based search engines Pubmed and Google Scholar with publication years 2017-2024. Result: After effleurage hand massage with lavender aromatherapy, the mother experienced mild fatigue. Conclusion: Effleurage hand massage with lavender aromatherapy is effective in reducing fatigue in postpartum mothers.